URGENSI PENDIDIKAN EKONOMI DALAM MEMBINA EKONOMI KREATIF - Pratiwi, Ngisti; Nindiawaty, Riza; Putra, Rachel Ahmadi; Sariatun, Sariatun (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2024)
This study aims to understand the urgency of economic education in fostering a creative economy. This research is a research library where data is obtained from various literature on economic education and the creative economy which is obtained through documentation techniques. The results of this study indicate that entrepreneurship, especially with regard to the creative economy, requires economic knowledge to be obtained through economic education. This economic education can be obtained through education carried out in educational institutions such as schools, seminars, courses, and competency development centers which can be found and obtained both online and offline. Knowledge about entrepreneurship can also be obtained through a community environment that discusses economic knowledge, for example HIPMI or the Indonesian Young Entrepreneurs Association and others.